(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Until about 1950, sugar was the first choice as coating agent for pharmaceutical preparations. As the tablets coating technique was changed from sugar coating to film coating, a number of polymers like Methyl Cellulose (MC), Hydroxy Propyl Methyl Cellulose (HPMC) and Ethyl Cellulose (EC) become the main coating materials in place of sugar. As for as aqueous coating materials are concerned, Sodium Carboxy Methyl Cellulose (Sod. CMC), Polyvinyl Acetate (PA), Polyvinyl Pyrrolidone (PVP), Sodium Alginate, Poly Ethyl Glycol and HPMC etc. are used either alone or in combination. Starch, especially amylose rich starch is known to have good film forming property. Therefore amylose rich starch is now-a-days used as aqueous based coating materials for pharmaceutical coating. It is successfully used for coating in combination with sorbitol and glycerol as plasticizer. A nine months study on prepared films justifies the stability of amylose rich starch. Both the dispersion and solution of amylose rich starch are used for coating purpose. The amylose rich starch composition for this is 70% amylose and 30% amylopectin. Aging problems are overcome by proper type and proper concentration of plasticizer. The coating with amylose rich starch provides safety, economic and ecological benefits.